Depression in Patients with Diabetes Mellitus-an Analytical Study in Rajshahi (TAJ: Journal of Teachers Association, 2021)
Background: Depression is one of the most common comorbid psychiatric disorders associated with diabetes mellitus (DM), and it impacts glycemic control. Optimal management of depression may lead to better control of glucose levels in DM.Objectives: The aim of this study was to assess depression in patients with DM and to compare it with healthy control and to determine the association of depression with glycemic control and socio-demographic profile in patients with DM and healthy control.Patients and methods: This cross-sectional comparative study was conducted among 140 patients with DM attending Rajshahi Medical College Hospital and Diabetic Association Hospital, Rajshahi, from July 2014 to June 2016. Subsequently, 140 age-matched healthy controls were included in this study. The DSM-V criteria were used to diagnose depression and the severity of depression was assessed by the Hamilton rating scale for depression. Blood glucose control was assessed by measuring HbA1c and categorized as: good glycemic control 8% considered as poor glycemic control.  Results: The proportion of depression was significantly higher in the patient (51, 36,4%) than in the control (20,14.3%) (X2= 18.256, df= 2, p 8%) compared to fair control (HbA1c 7-8%) (p